Societies of Futures Past: Examining the History and Potential of International Society Collaborations in Addressing the Burden of Rheumatic Heart Disease in the Developing World - Zachary Obinna Enumah; Percy Boateng; Ralph Morton Bolman; Ralph Morton Bolman; Friedhelm Beyersdorf; Friedhelm Beyersdorf; Friedhelm Beyersdorf; Liesl Zühlke; Liesl Zühlke; Liesl Zühlke; Liesl Zühlke; Maurice Musoni; et al. (Frontiers in Cardiovascular Medicine, 2021)
This paper explores the role and place of national, regional, and international society collaborations in addressing the major global burden of rheumatic heart disease (RHD). On the same order of HIV, RHD affects over 40 million people worldwide. In this article, we will outline the background and current therapeutic landscape for cardiac surgery in low- and middle-income countries (LMICs) including the resource-constrained settings within which RHD surgery often occurs. This creates numerous challenges to delivering adequate surgical care and post-operative management for RHD patients, and thus provides some context for a growing movement for and applicability of structural heart approaches, innovative valve replacement technologies, and minimally invasive techniques in this setting. Intertwined and building from this context will be the remainder of the paper which elaborates how national, regional, and international societies have collaborated to address rheumatic heart disease in the past (e.g., Drakensberg Declaration, World Heart Federation Working Group on RHD) with a focus on primary and secondary prevention. We then provide the recent history and context of the growing movement for how surgery has become front and center in the discussion of addressing RHD through the passing of the Cape Town Declaration.